INSTILLING AKHLAKUL KARIMAH VALUES IN STUDENTS THROUGH DIBA' READING ACTIVITIES AT DARUL 'ULUM ISLAMIC BOARDING SCHOOL JOMBANG - Reni Sukmawati; Mukhlisin; Anna Qomariana (ELite Journal : International Journal of Education, Language and Literature, 2026)
This research is based on the fact that instilling Akhlakul Karimah (noble character) values is the main goal of education in Islamic boarding schools to shape students with good morals. The development of the times and various environmental influences require habituation that can continuously strengthen students' character. One effort applied at the Muzamzamah Female Dormitory XI is the Diba' reading activity, which contains examples of the Prophet Muhammad's noble character and religious values practiced in daily life. This study aims to describe the implementation, influence, and evaluation results of instilling Akhlakul Karimah values in students through Diba' reading activities. The research uses a qualitative approach with a descriptive design. Data were obtained through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data condensation, data presentation, and conclusion drawing. The results show that the instillation of Akhlakul Karimah values is carried out through habituation, role modeling, guidance, supervision, and continuous evaluation by caregivers and female teachers. The Diba' reading activity has a positive influence on student character formation, especially in fostering religious attitudes, discipline, responsibility, politeness, patience, and togetherness, so that Akhlakul Karimah values become more embedded in students' behavior in the boarding school environment and daily life. Although the implementation still faces some obstacles, such as differences in students' ability to read Diba' and lack of concentration among some students, these obstacles are overcome through continuous guidance and mentoring.